Physiological and Phytochemical Responses of Spinach Baby Leaves Grown in a PFAL System with LEDs and Saline Nutrient Solution - Filippos Bantis; Mariangela Fotelli; Zoran S. Ilić; Athanasios Koukounaras (Agriculture, 2020)
Spinach is a leafy vegetable containing a plethora of bioactive compounds. Our study aimed to evaluate the physiological (i.e., JIP-test) and phytochemical response of spinach baby leaves grown with regular or mildly saline (40 mM NaCl) nutrient solution and irradiated by four light-emitting diodes (LEDs) with broad spectra. T1 (highest red and far-red, low blue) and T3 (high red, balanced blue, green and far-red) led to a better developed photosynthetic apparatus compared to T2 (red peak in 631 nm) and T4 (highest blue and green), highlighted by PIABS and its structural components: RC/ABS, φP0, ψE0, and ΔVIP. Elevated salinity only affected the latter parameter. T1 induced the maximum yield production but also the highest nitrate content which was far below the maximum level permitted by European legislation. Regardless of salinity level, T3 enhanced total phenol, chlorophyll, and carotenoid content. T2 and T4 led to inferior nutritional quality. Non-saline nutrient solution promoted the chlorophyll and carotenoid contents and the antioxidant potential, regardless of light treatment. By contrast, soluble sugar content was enhanced by saline nutrient solution. Our study shows that physiology and nutritional quality of spinach baby leaves can be manipulated by small interplays in the light spectra and salinity level.